Rare and unusual isolates of viridans streptococci from the human oral cavity - Shree Dhotre; Namdev Suryawanshi; Basavraj Nagoba; Sohan Selkar (Wolters Kluwer Medknow Publications, 2016)
Context: The genus Streptococcus consists of more than 65 species. The taxonomic classification of these members is not well-defined. Among the viridans group streptococci (VGS), there are major taxonomic changes by the addition of many new species; whereas, most of the new strains are of animal origin and only a few have been reported to be isolated from humans. Rare and unusual species of VGS such as Streptococcus thoraltensis, S. pluranimalium and S. hyointestinalis are normally associated with different animals. Their isolation from human being is not yet reported. Aim: To find out the rare and unusual species of viridans group streptococci from human oral cavity. Settings and Design: A case-controlled study carried out at hospital-based dental services in a tertiary care hospital. Materials and Methods: Subgingival plaque samples of the tooth were collected from 80 patients (34 with periodontitis and 46 without periodontitis) undergoing tooth extraction. Cultures were subcultured onto special media such as Tryptone Soya blood Agar supplemented with strepto supplement and Mutans-Sanguis Agar. Identification of strains and antimicrobial susceptibilities were measured as minimum inhibitory concentration using Vitek 2 (BioMérieux, Paris, France) automated system. Results: We have identified three strains of VGS - S. thoraltensis, S. pluranimalium and S. hyointestinalis from subgingival plaque samples from patients with periodontitis. S. thoraltensis and S. pluranimalium were found to be resistant to most of the antibiotics. Conclusions: To the best of our knowledge, this is the first report of isolation of these rare and unusual strains from the human oral cavity.